Agnolo Bronzino : Medici court artist in context - Bronzino, Agnolo, 1503-1572; Gáldy, Andrea M. (Cambridge Scholars, 2013)
"The Florentine artist Agnolo Bronzino (1503-1572) has long been celebrated as the consummate court painter and his sumptuous portrayals of Duke Cosimo de' Medici and Duchess Eleonora de Toledo have become icons of Italian Renaissance art. In this volume, an international assembly of scholars advances modern perceptions of Bronzino's art by applying fresh research paradigms not only to the well-known portraits, but also to other painted subjects, frescoes, and tapestries within the context of ancient Roman precedents, Renaissance European court culture, and postmodernist theory. The seven essays supplement two recent Bronzino exhibitions in New York and Florence (2010) by addressing Bronzino's portraiture, creative process, and tapestry production as well as past and present attitudes towards nudity, sexuality, landscapes, and poetic satire in Bronzino's imagery."--Pub. desc